2012
DOI: 10.1080/08952841.2012.639676
|View full text |Cite
|
Sign up to set email alerts
|

How Women in Late Midlife Become Caregivers for Their Aging Parents

Abstract: Approximately 52 million Americans provide informal (unpaid) care to a family member or friend who is disabled or ill. The most common informal caregiving relationship is that of an adult child providing assistance to an aging parent. This article describes a qualitative study examining how adult daughters between the ages of 50 and 65 become caregivers to their parent or parent-in-law. Data were collected through in-depth, face-to-face interviews with 15 female caregivers. Analysis revealed that assistance pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 15 publications
3
13
0
Order By: Relevance
“…This finding also signifies a trend that reflects the typical informal caregiving arrangements for this age group (e.g., see Pope, Kolmer, & Glass, 2012). Qualitative data also showed that the health status of elderly parents was critical in perceptions of caregiving stress, supporting previous work showing that parents in poorer health more likely receive care from an adult child than those who are healthier (Himes, Jordan, & Farkas, 1996).…”
Section: Discussionsupporting
confidence: 62%
“…This finding also signifies a trend that reflects the typical informal caregiving arrangements for this age group (e.g., see Pope, Kolmer, & Glass, 2012). Qualitative data also showed that the health status of elderly parents was critical in perceptions of caregiving stress, supporting previous work showing that parents in poorer health more likely receive care from an adult child than those who are healthier (Himes, Jordan, & Farkas, 1996).…”
Section: Discussionsupporting
confidence: 62%
“…A possible explanation for this finding is based on the distinct roles of men and women. Despite the far‐reaching changes in gender roles today, young women are still the primary caregivers to their children (Nordenmark, ), and older women serve as caregivers for aging family members more so than men do (Pope, Kolomer, & Glass, ). In light of the caregiving role, which demands time and energy resources, women expressed lower intentions to volunteer than men in two of the dimensions examined.…”
Section: Discussionmentioning
confidence: 99%
“…In other conditions, the importance of the carers' help has also been highlighted [51][52][53][54][55]. Despite some studies that suggest carers embraced their role in variable ways [51,54,55], in part explained by the types of relationship (i.e.…”
Section: Discussionmentioning
confidence: 99%